Molecular dynamics simulations of Krytox-Silica-Nafion composite for high temperature fuel cell electrolyte membranes - Yana J. (2014)
A five percent by weight of carboxylic acid terminated perfluoropolyether hybrid with silica (Krytox-Silica) in Nafion composite polymer was used in the modification of a polymer electrolyte fuel cell membrane in order to improve its efficiency at high operating temperatures. Molecular dynamics (MD) simulations were carried out in order to understand the microscopic properties of two systems, Krytox-Silica in Nafion and pure Nafion. A model of five percent Krytox-Silica in a Nafion composite polymer consisting of 15 Nafion side chains, 15 hydronium ions and one of Krytox-Silica was used. In another system, pure Nafion was modeled without Krytox-Silica. Models with various amounts of water molecules and temperatures were simulated to study the water content and temperature effects. The results were in good agreement with the experiments and could be used to describe the application of Krytox-Silica-Nafion composite at high temperatures. The effect of the amount of water molecules on the diffusion coefficient or proton conductivity showed more deviations between 5% wt of Krytox-Silica-Nafion composite and pure Nafion system at lower water content (or higher temperature) than at high water content (or low temperature). According to the diffusion coefficient results, the percentage of water molecules at each temperature corresponded to the known experimental trend. Silica, as the water absorbent in the hybrid polymer membrane, did not have a strong interaction with water molecules or H3O+ ions; thus the proton conductivities will not be highly affected by adding Krytox-Silica to the Nafion. © 2010 Elsevier Ltd.